Analisis Penerimaan Aplikasi Transportasi Online GoRide dan GraBike Menggunakan Metode UTAUT di Kota Surabaya - Aprilia Nurul Fatihah; Sulis tiowati; Ayouvi Poerna Wardhanie (Jurnal Sistem Informasi Universitas Dinamika, 2020)
The presence of online transportation applications that allow transportation services to be ordered and paid online has been rife in Indonesia, especially in the city of Surabaya. One of the transportation that can be ordered online is motorcycle taxi. Applications that provide online motorcycle transportation services are GoRide and GraBike. Currently there are differences in user acceptance of the GoRide and GraBike online transportation applications in the city of Surabaya due to the advantages and disadvantages of each application. To overcome these problems, researchers will evaluate the level of acceptance of GoRide and GraBike online transportation application users, which focus on Gojek and Grab users in the city of Surabaya using the UTAUT method. This study aims to determine the factors that influence user acceptance of GoRide and GraBike online transportation applications. The variables in the UTAUT method used to analyze consist of six variables, namely Performance Expectancy, Business Expectancy, Social Influence, and Facilitating Conditions in influencing users' perceptions of interest behave (Behavioral Intention) to use technology (Use Behavior).